Education Planning “Need to Knows” for Military Families - Barbara O'Neill; Martie Gillen; Kristen Jowers (EDIS)
This publication discusses general information about education costs, savings plans, and payment methods, military-specific educational benefit programs, military-specific laws and policies affecting student loan repayment, five education planning tips for military families, and education planning resources. Written by Barbara O’Neill, Martie Gillen, and Kristen Jowers, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.